John Steinbeck in Kiev. - Unknown:::Creator::::::::::::
John Steinbeck looks at a statue with Frida Lurie (Russian interpreter) in what was then called The Museum of Western and Oriental Art (now Ukraine's Bogdan and Varvara Khanenko Museum of Art) The original is in the safe.